2007
DOI: 10.1175/jpo3105.1
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Mesoscale Dipole Frontal Collisions

Abstract: Frontal collisions of mesoscale baroclinic dipoles are numerically investigated using a three-dimensional, Boussinesq, and f-plane numerical model that explicitly conserves potential vorticity on isopycnals. The initial conditions, obtained using the potential vorticity initialization approach, consist of twin baroclinic dipoles, balanced (void of waves) and static and inertially stable, moving in opposite directions. The dipoles may collide in a close-to-axial way (cyclone-anticyclone collisions) or nonaxiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…This description of an elastic interaction contributes to several previous studies involving eddy‐pair interactions, including interactions of dipoles with solid boundaries (de Ruijter et al., 2004; Kloosterziel et al., 1993; Tenreiro et al., 2006; Verzicco et al., 1995; Voropayev & Afanasyev, 1992; Zavala Sansón & Gonzalez, 2021), interactions of dipoles with inertia–gravity waves (Claret & Viúdez, 2010; Huang et al., 2017), and dipole‐dipole interactions (Dubosq & Viúdez, 2007; McWilliams & Zabusky, 1982; Meleshko & van Heijst, 1994; Velasco Fuentes & van Heijst, 1995; Voropayev & Afanasyev, 1992). In the cases of dipole‐dipole and dipole‐vortex interactions both elastic and inelastic processes are possible depending on the initial vorticity distribution, which includes the location, orientation and vorticity distributions of the eddies (Aref, 1979; Meleshko & van Heijst, 1994).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This description of an elastic interaction contributes to several previous studies involving eddy‐pair interactions, including interactions of dipoles with solid boundaries (de Ruijter et al., 2004; Kloosterziel et al., 1993; Tenreiro et al., 2006; Verzicco et al., 1995; Voropayev & Afanasyev, 1992; Zavala Sansón & Gonzalez, 2021), interactions of dipoles with inertia–gravity waves (Claret & Viúdez, 2010; Huang et al., 2017), and dipole‐dipole interactions (Dubosq & Viúdez, 2007; McWilliams & Zabusky, 1982; Meleshko & van Heijst, 1994; Velasco Fuentes & van Heijst, 1995; Voropayev & Afanasyev, 1992). In the cases of dipole‐dipole and dipole‐vortex interactions both elastic and inelastic processes are possible depending on the initial vorticity distribution, which includes the location, orientation and vorticity distributions of the eddies (Aref, 1979; Meleshko & van Heijst, 1994).…”
Section: Discussionmentioning
confidence: 96%
“…Many geophysical processes occur on approximately horizontal scales, where the vertical, gravity oriented, velocity component is several orders of magnitude smaller than the horizontal velocity component (Wayne, 2011). For example, in the case of dipole‐dipole interactions, Dubosq and Viúdez (2007) investigated numerically non‐axial frontal collisions of mesoscale baroclinic eddy‐pairs as well as 2D eddy‐pair collisions, and concluded that the 3D inelastic interaction processes were qualitatively similar to the 2D interactions, as long as, the eddies had a similar vertical extent. In this study, where we deal with elastic interactions, the 2D processes are expected to be dominant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial asymmetry in the prescribed a Z ± is due to the fact that these vortices are defined in the initial (reference) configuration which has flat isopycnals. During the initialization time the isopycnals stretch (shrink) in the anticyclone (cyclone), so that at the end of the initialization period ( t i = 5 T ip ) the vortices have a similar vertical extent in the physical space and the dipole describes a straight trajectory [ Dubosq and Viúdez , 2007]. The horizontal velocity, which is slightly larger in the anticyclone than in the cyclone, reaches maxima ∣ u h ∣ max = 0.78 at the dipole center (Figure 14b).…”
Section: Dipole‐wave Interactionmentioning
confidence: 99%
“…To mention just a few, some have addressed the dipole formation [ van Heijst and Flór , 1989; Mied et al , 1991; Spall and Robinson , 1990; Kloosterziel and van Heijst , 1991; Spall , 1995; Orlandi and Carnevale , 1999; Sansón et al , 2001; Feng et al , 2007], the dipole structure [ Norbury , 1973; Fedorov and Ginsburg , 1986; Couder and Basdevant , 1986; Sheres and Kenyon , 1989; Simpson and Lynn , 1990; Carton , 2001], and dipole dynamics [ Pierrehumbert , 1980; Rasmussen et al , 1996; Eames and Flór , 1998; Kizner et al , 2003; Pallàs‐Sanz and Viúdez , 2007]. Other investigations have focused on their interaction, namely dipole‐dipole interaction [ McWilliams and Zabusky , 1982; van Heijst and Flór , 1989; Velasco Fuentes and van Heijst , 1995; Dubosq and Viúdez , 2007], dipole‐topography interaction [ Kloosterziel et al , 1993; Carnevale et al , 1997], and dipole‐wave interaction [ Godoy‐Diana et al , 2006].…”
Section: Introductionmentioning
confidence: 99%